The concurrence of pension and disability insurance of the contractor selected issues - Krajewski, Marcin (Acta Universitatis Lodziensis. Folia Iuridica, 2019)
The paper provides an analysis of advantages and disadvantages of being subject to social insurance by the contractors, under the Act on the social insurance system of 13 October 1998. The focus is placed on the principles of concurrence of titles in pension and disability insurance. The paper also provides an analysis of the current model of accumulation of titles in social insurance. In the last section of the paper the author presents the alternative model of consistently charging a premium on income of the insured.